A STUDY ON THE PERCEPTION OF STUDENTS IN A HIGHER LEARNING INSTITUTION TOWARDS COLLABORATIVE LEARNING - NoorAileen Ibrahim; NoorLida Daud; Nurul Shima Taharuddin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In the fast-paces world when we live in today, learners face various problems in the classroom. They are often unmotivated, anxious and helpless because they lack the support and encouragement they need. The purpose of the study is to examine the diploma students’ perception of collaborative learning since most students were initially found to be reluctant about group work due to numerous factors. Collaborative Learning (CL) is a pedagogical practice that facilities socialization which leads to academic achievement and has been well documented. A survey through questionnaire is distributed to 100 students from two faculties currently undergoing diploma studies at a local institute of higher learning. Data from the study indicated that the students had positive experiences with CL and a number of them believe that their lecturers helps them to develop a sense of cooperation through CL. The work presented here has implications for future studies of addressing issues related to collaborative learning and might one day help find the appropriate learning style for undergraduates.